Galacto-oligosaccharides alleviate experimental lactose intolerance associated with gut microbiota in mice - Li, Qianxi; Wang, Xinlei; Guo, Siyu; Wang, Tongtong; Cao, Heng; Cao, Yunhe; Dong, Bing (Frontiers in Microbiology, 2025)
IntroductionGalacto-oligosaccharides (GOS) are beneficial for alleviating lactose intolerance (LI). GOS have the ability to modify the composition of the intestinal microbiota. The development of intestinal diseases could be influenced by the composition of the gut microbiota. Nevertheless, it remains unclear whether gut microbiota exerts an effect when GOS alleviate LI, whether alterations in composition of the intestinal microbiota influence inflammatory response and lactose digestion.MethodsWe first investigated the effects of GOS on mice with established lactose intolerance. Next, we demonstrated that prophylactic supplementation with GOS also conferred similar benefits.ResultsThe results showed that GOS enhanced anti-inflammatory, antioxidant, and gut barrier function. We observed that GOS mediated a change in the gut microbiome by increasing the abundance of Lactobacillus. GOS pre-supplementation reduced incident LI, enhanced anti-inflammatory, antioxidant, and gut barrier function, and markedly altered the gut microbiome by significantly enriching Bifidobacterium. Collectively, the alleviation of LI by GOS suggests an intimate involvement of probiotics.DiscussionThis study demonstrates that GOS ameliorated LI in a gut microbiota-dependent manner. Our findings provide novel evidence that GOS substitute for lactase and serve as a potential modulator of the gut microbiota for the prevention of LI.